Exploring students conceptual understanding of forces - Perez, Roberto S. (Animo Repository, 2005)
The study attempted to explore student's conceptual understanding and to determine the most prevalent misconceptions of force and motion among senior students of Makati High School, Paranaque National High School and Pasay City West National High School. The instrument used was a modified 25-item open-ended Force Concept Inventory. To interpret the qualitatively, the researcher utilized the written explanations together with the unstructured interview. Results revealed homogeneity of the open-ended FCI scores. None of the respondents reach the entry threshold of being a Newtonian thinker. The respondents are found to manifest the following misconceptions (a) velocity proportional to force, velocity from acceleration, greater mass implies greater force, most active agent produces greater force, last force to act determines motion all of which has an average misconception index of above 60% on each of these concepts. Likewise, majority of the respondents exhibited unrecognition of inertial motion. Other alternative conceptions fall in the categories not found in the multiple choice FCI test.